2017
DOI: 10.1037/neu0000331
|View full text |Cite
|
Sign up to set email alerts
|

Dual tasking in Parkinson’s disease: Cognitive consequences while walking.

Abstract: Objective Cognitive deficits are common in Parkinson’s disease (PD) and exacerbate the functional limitations imposed by PD’s hallmark motor symptoms, including impairments in walking. Though much research has addressed the effect of dual cognitive-locomotor tasks on walking, less is known about their effect on cognition. The purpose of this study was to investigate the relation between gait and executive function, with the hypothesis that dual tasking would exacerbate cognitive vulnerabilities in PD as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 74 publications
4
30
1
2
Order By: Relevance
“…As expected [11], the combination of the fluency task with pedaling, a pure motor task largely preserved in PD patients [29,30], seems to be responsible for the similarity in fluency performance regardless of the experimental condition. In addition, all performance differences by condition for fluency when combined with tracking, pedaling when combined with fluency, and tracking when combined with fluency were neutralized when the cognitive status measure was included in the model as a covariate, supporting the suggestion that dual costs in PD could be largely related to cognitive status even for those associated to the almost pure motor task, namely, the pedaling task [7][8][9]. Parkinson's Disease…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…As expected [11], the combination of the fluency task with pedaling, a pure motor task largely preserved in PD patients [29,30], seems to be responsible for the similarity in fluency performance regardless of the experimental condition. In addition, all performance differences by condition for fluency when combined with tracking, pedaling when combined with fluency, and tracking when combined with fluency were neutralized when the cognitive status measure was included in the model as a covariate, supporting the suggestion that dual costs in PD could be largely related to cognitive status even for those associated to the almost pure motor task, namely, the pedaling task [7][8][9]. Parkinson's Disease…”
Section: Discussionmentioning
confidence: 68%
“…us, voluntary movements in everyday life rarely are wholly automatic and therefore impose cognitive demands that could impair cognitive performance [6]. Conversely, because of loss of movement automaticity in PD, higher demands in attentional resources seem to be expected to maintain movement amplitude, rhythm, or posture [7,8]. As some attentional resources must be allocated to the voluntary movement, performing a concurrent cognitive task may well interfere in the motor performance of PD patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite our study being limited to healthy, young adults, there seems to be enough evidence to suggest that similar time–frequency, perturbation-evoked EEG activity should be studied in patient populations. While Parkinson’s disease has been primarily associated with basal ganglia dysfunction ( Blandini et al, 2000 ), dual-task studies have indicated that cortical activity is also affected ( Yogev et al, 2005 ; Salazar et al, 2017 ), making EEG a potentially relevant recording site. It is also interesting to note similarities between our perturbation time–frequency pattern and the gait-related time–frequency pattern seen in other studies during foot–ground contact and initial stance ( Gwin et al, 2011 ; Seeber et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…38 In studies using the dual-task paradigm, patients with PD showed greater dual-task interference in both cognitive and gait tasks compared with that of age-matched healthy controls. 39 Under dual-task conditions, gait kinematics including cadence, stride length, gait velocity, and arm swing were also reduced compared with those under singletask conditions. 40 Moreover, it is also suggested that high cognitive and postural dual-task cost is associated with the presence of gait freezing.…”
Section: Cog Nitive Interferen Ce On P Os Tur Al /Lo Comotor Ta S Kmentioning
confidence: 93%